GALILEU GALILEI: SCIENCE WITH SOCIAL AND POLITICAL IMPLICATIONS - Barbosa, Cloves; Wilson Tafner Junior, Armando (Revista Gênero e Interdisciplinaridade, 2024)
This paper has the goals to introduce the Galilei’s contribution to science. Galilei leaved in medieval historical time. He took the Francis Bacon’s theory to make observation on skay. Galilei was a big creator of instruments to research. Galilei invented a series of instruments during your life. He involved in the context of the theories of geocentrism e heliocentrism. Because this, Galilei was problems with ecclesiastical power.